Culture change and culture loss among youths in Sabah: Some observations in Dusunic societies - Jacqueline Pugh-Kitingan (Borneo Research Council, Inc, 2024)
This paper focuses on the effects of culture change on genres of intangible cultural heritage and elements of traditional knowledge among youths from specific Dusunic ethnic groups of Sabah, Malaysia’s northernmost state located on Borneo island. Based on over four decades of observation and research, it discusses the reasons for the decline in traditional vocal music and secular solo instrumental genres among the young in some cultures, as opposed to the continuing importance of gong ensemble performances. It also touches on changes in heritage language use, changes in agricultural practices, and other issues causing loss of traditional knowledge among youths. In addition to these, it looks at ways in which societies and groups have undertaken to preserve their cultures for younger generations. These range from classes in traditional music, a move towards indigenous languages in kindergartens and schools, and cultural festivals including the State Ka’amatan or Harvest Festival. The latter has seen not only traditional expressions of music, dance and sports, but the invention of new “traditions” and new “mythology” through the Unduk Ngadau pageant.